Scientific publications in peruvian journals of psychology: an analysis from student participation - Hernández, Ronald M. (2019)
The study describes the scientific production of psychology students in Peruvian Psychology Journals registered in the Latindex directory in 2017. A theoretical study that analyzed 220 articles from 12 journals of psychology was carried out. Any publication that did not have the IMRAD structure was excluded. There were 485 authors with national and international affiliation, of which 8.25% were psychology students and had participated in the publication of 29 articles (original research, reviews, and case studies). Of the 29 articles with student authorship, 64.5% were articles from the clinical area and 35.5% from the educational area. The most prevalent type of research was instrumental (54.8%). It is concluded that the scientific production of undergraduate psychology students in psychology journals is low. This makes it necessary to strengthen and encourage the generation and dissemination of psychology scientific studies by students in Peru.